1986
DOI: 10.1111/j.1751-1097.1986.tb05608.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Synthetic Bacteriorhodopsin Pigments. Further Probes of the Chromophore Binding Site

Abstract: Abstract— A series of retinals with specific structural alterations have been synthesized to probe the bacteriorhodopsin binding site. The 4‐chloro‐, 4‐bromo‐ and 4‐iodoretinals all form pigments with bacterioopsin but undergo an in situ displacement of the allylic halogen to form the 4‐hydroxyretinal pigment. Several naphthyl retinals were prepared which effectively extend the polyene chain and/or add bulk to the ring portion of the chromophore. All the naphthyl retinals form pigments with bacterioopsin but o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…There are, however, no indications of deviation from the trend of longitudinal flexibility noted for the C-17 and the C-22 BR analogs. Among other examples of analogs with modified polyene chain length, particularly pertinent is a series of naphthalene-retinal analogs (Crouch et al, 1986). The latter results appear to be consistent with the ideas presented here.…”
supporting
confidence: 86%
“…There are, however, no indications of deviation from the trend of longitudinal flexibility noted for the C-17 and the C-22 BR analogs. Among other examples of analogs with modified polyene chain length, particularly pertinent is a series of naphthalene-retinal analogs (Crouch et al, 1986). The latter results appear to be consistent with the ideas presented here.…”
supporting
confidence: 86%
“…Literature on bR analog studies indeed reveals that the hydrophobic binding site of bR is not as restrictive as the visual pigment, e.g., capable of accepting chain-lengthened (i.e., ring-displaced) 10 and extensively ring-modifed analogs (naphthyl, 11 ringopened, 12 azulenic 13,14 ). A possible consequence of diminished protein inhibition is dynamic NMR behavior for these signals.…”
Section: Discussionmentioning
confidence: 96%
“…These studies have provided significant information on the steric and electronic properties of the chromophore binding site. The trimethyl cyclohexenyl ring of the native retinal (6) has been replaced by the phenyl (6)(7)(8), naphthyl (9)(10)(11)(12) and phenanthryl (13) rings (Fig. l), and it was concluded that the ring binding site is unrestrictive, at least to these systems.…”
Section: Introductionmentioning
confidence: 99%